Design of Nanoparticle-Based Carriers for Targeted Drug Delivery. (9th June 2016) - Yu, Xiaojiao; Trase, Ian; Ren, Muqing; Duval, Kayla; Guo, Xing; Chen, Zi
Abstract : Nanoparticles have shown promise as both drug delivery vehicles and direct antitumor systems, but they must be properly designed in order to maximize efficacy. Computational modeling is often used both to design new nanoparticles and to better understand existing ones. Modeled processes include the release of drugs at the tumor site and the physical interaction between the nanoparticle and cancer cells. In this paper, we provide an overview of three different targeted drug delivery methods (passive targeting, active targeting, and physical targeting) and compare methods of action, advantages, limitations, and the current stages of research. For the most commonly used nanoparticle carriers, fabrication methods are also reviewed. This is followed by a review of computational simulations and models on nanoparticle-based drug delivery.